Jack Grout : a legacy in golf : pioneer tour pro and teacher to Jack Nicklaus - Grout, Dick (Blue River Press, 2012)
The author presents the life story of Jack Grout, from his childhood in middle-class Oklahoma, to his PGA tournaments playing against Ben Hogan, Byron Nelson, Sam Snead and Gene Sarazen, to his role as golf teacher to Raymond Floyd, David Graham, Lanny Wadkins, and, for 39 years, to Jack Nicklaus.